(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Maxillofacial injuries are among the most typical forms of body injuries. Facial bone fractures, dentoalveolar injuries and soft tissue injuries are the three categories of maxillofacial injuries. Automobile accidents, attacks, falls, and athletic injuries are all possible causes. This study aimed to determine the role of helmet use on the severity of oral maxillofacial injuries among electric bike and motorcycle accidents attending Hafr Central Hospital, Saudi Arabia. Materials and methods: This study was a descriptive study of the injured motorcyclist, electric power bikes, and scoters seen with maxillofacial injuries between January 2021 and January 2023 at Emergency Hafr central hospital in Hafr albaten city. The study was a cross-sectional study that included patients reported within the previous three years. The source population consisted of maxillofacial injury patients who presented to the accident department after being involved in an electric-powered bike, scooter, or motorbike accident, as well as the oral and maxillofacial surgery department at Hafr Cental hospital in Eastern Provence. Data were entered into Microsoft Excel soft Simple descriptive statistical, chi-square test, and Kruskal-Wallis test was applied as appropriate. Statistical significance was inferred at p<0.05. Results: The study included 154 maxillofacial injury patients in case of motorcycle accidents; all of them (100%) were non-helmeted. The injured patients were in different age categories (less than 5 to more than 20 years old). However, most patients were between 10-14 years old (91). The majority of injured patients in motorcycle accidents were males (n=108), while only 46 injured women were reported. Most of the injuries were soft tissues in male patients (106) or females (46). Only 2 males had hard tissue injuries. The most common facial injuries were Lip injury (39), followed by Frontal laceration (21), Cheek abrasion (17), and Frontal bruises (16), then Nasal laceration (14) and Scalp laceration (13). Suturing was carried out on the majority of injured patients (132, 85.71%), while 19 patients (12.3%) had no treatment, and 3 patients (1.95%) had Oculoplastic surgery. Conclusion: Motorcyclists, electric power bikes, and scooter riders who used helmets had a lower risk of head injury, as well as hard tissue and maxillofacial injuries. These findings might lead to more effective legislation and control of helmet use, as well as better treatment regimens for general and dental physicians.